Timing of food introduction and development of food sensitization in a prospective birth cohort. Issue 5 (1st August 2017) - Tran, Maxwell M.; Lefebvre, Diana L.; Dai, David; Dharma, Christoffer; Subbarao, Padmaja; Lou, Wendy; Azad, Meghan B.; Becker, Allan B.; Mandhane, Piush J.; Turvey, Stuart E.; Sears, Malcolm R.; ,
Abstract: Background: The effect of infant feeding practices on the development of food allergy remains controversial. We examined the relationship between timing and patterns of food introduction and sensitization to foods at age 1 year in the Canadian Healthy Infant Longitudinal Development (CHILD) birth cohort study. Methods: Nutrition questionnaire data prospectively collected at age 3, 6, 12, 18, and 24 months were used to determine timing of introduction of cow's milk products, egg, and peanut. At age 1 year, infants underwent skin prick testing to cow's milk, egg white, and peanut. Logistic regression models were fitted to assess the impact of timing of food exposures on sensitization outcomes, and latent class analysis was used to study patterns of food introduction within the cohort. Results: Among 2124 children with sufficient data, delaying introduction of cow's milk products, egg, and peanut beyond the first year of life significantly increased the odds of sensitization to that food (cow's milk adjOR 3.69, 95% CI 1.37‐9.08; egg adjOR 1.89, 95% CI 1.25‐2.80; peanut adjOR 1.76, 95% CI 1.07‐3.01). Latent class analysis produced a three‐class model: early, usual, and delayed introduction. A pattern of delayed introduction, characterized by avoidance of egg and peanut during the first year of life, increased the odds of sensitization to any of the three tested foods (adjOR 1.78, 95% CI 1.26‐2.49). Conclusions: Avoidance of potentially allergenic foods during the first year of life significantly increased the odds of sensitization to the corresponding foods. Abstract :